Factor Analysis of Teenage Athletes' Goal Orientations and Sports Participation Motives in Leisure Time - Noshin Benar; Mohsen Loghmani (The Society of Aging and Physical Activity (SAPA), 2014)
The aim of the present study was to identify the most important goal orientations and sport participation motives among teenage athletes in leisure time. In addition, these variables were prioritized and associations between all constructs have been studied. For this purpose, 376 Iranian teenage athletes were singled out by cluster-random sampling, and responded to Task and Ego Orientation Sport Questionnaire (T.E.O.S.Q), and Participation Motivation Questionnaire (PMQ). The results of Confirmatory Factor Analysis (CFA) showed fit model indexes for twosome dimensions of sport goals, and five motives of sport participation (RMSEA ≤ .06; χ2 / df ≤ 3; Goodness Indexes≥ .90). Based on CFA and loadings, goals of task-orientation (r= .93) and ego-orientation (r= .43) were identified for sport goals, and motives of energy release (r= .94), status (r = .76), fitness (r= .48), team atmosphere (r= .46), and skill development (r= .26) obtained for teenagers' sport participation, respectively. In general, the findings of the present study provided the adequate understanding for sport managers, coaches, physical educators and their parents by how sport motivation of teenagers, via satisfying teenager's motives specially motives of energy release and status, provided their satisfaction and gratification during long life.